Effects of a fixed-dose combination of enalapnl and hydrochlorothiazide on carotid intima-media thickness in patients with arterial hypertension - O. D. Ostroumova (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To investigate the effects of Co-renitek (enalapril 20 mg + hydrochlorothiazide 12,5 mg) on carotid artery (CA) intima-media thickness (IMT) in patients with Stage II-III essential arterial hypertension (EAH).Material and methods. In total, 44 patients with Stage II-II AH were examined (mean age 59,2±7,7 years; Stage II and II AH in 43,2% and 56,8%, respectively). At baseline and during the treatment phase, blood pressure (BP) measurement and duplex CA ultrasound were performed. All participants received Co-renitek (1 tablet daily, taken in the morning). If target BP levels (<140/90 mm Hg) were not achieved in 4 weeks, the daily dose was increased up to 2 tablets. The follow-up lasted for 48 weeks.Results. A significant (p<0,05) reduction in office BP levels was observed — by 23,2 mm Hg for systolic BP (SBP), and by 11,5 mm Hg for diastolic BP (DBP). At baseline, increased CA IMT was registered in 32 individuals. After 48 weeks of the treatment, IMT significantly decreased for both CA — by 11% for right CA, and by 6% for left CA. For left CA, IMT decreased or normalised in 50% of the participants, remained the same in 31%, and increased in 19%. For right CA, IMT normalised in 25%, decreased in 57%, and increased in 9%.Conclusion. In Stage II-III AH patients treated for 48 weeks, a fixed-dose combined antihypertensive therapy with Co-renitek resulted in a significant reduction of SBP and DBP, as well as in bilateral CA IMT reduction.